THE RELATIONSHIP BETWEEN STUDENT PERCEPTIONS IN UTILIZING OBS VIDEO MEDIA AND STUDENT MOTIVATION TO LEARNING OUTCOMES - Misbah Fikrianto; Agus Susanto (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aims to determine the relationship between student's perceptions of the use of video OBS learning media and student learning motivation partially and collectively toward social studies learning outcomes. This research uses quantitative research, survey methods, and correlational techniques. The target population is junior high school students in Depok City. The sample in this study were Grade VIII students at Raudlatul Falah Middle School, Darul Ulum Middle School, and PGRI 363 Pondok Petir Middle School, taking samples using a random sampling technique. The study results were: 1) There was a positive relationship between students' perceptions of using video OBS learning media on social studies learning outcomes for students at SMP Bojong Sari Depok, 55%. 2) There is a positive relationship between student learning motivation and social studies learning outcomes for students at SMP Bojong Sari Depok 51%. 3) There is a positive relationship between student's perceptions of the use of video OBS learning media and students' learning motivation, together with the results of learning history in students at SMP Bojong Sari Depok 40%.